2010
DOI: 10.1162/jocn.2009.21207
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Occipito-temporal Contributions to Reading with TMS

Abstract: Abstract■ The debate regarding the role of ventral occipito-temporal cortex (vOTC) in visual word recognition arises, in part, from difficulty delineating the functional contributions of vOTC as separate from other areas of the reading network. Here, we investigated the feasibility of using TMS to interfere with vOTC processing in order to explore its specific contributions to visual word recognition. Three visual lexical decision experiments were conducted using neuronavigated TMS. The first demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 92 publications
6
46
1
Order By: Relevance
“…An additional seven participants were excluded after analyzing their data from the visual lexical decision TMS experiment. 11 of 18 participants who received vOTC stimulation showed the expected slowdown on words, with an average increase of 40 ms for TMS relative to no-TMS trials (t (10) ϭ 4.0, p ϭ 0.003), similar to that seen previously (Duncan et al, 2010). The remaining seven either showed no effect of TMS or had faster RTs with stimulation, probably due to a nonspecific intersensory facilitation.…”
Section: Occipitotemporal Tmssupporting
confidence: 74%
See 1 more Smart Citation
“…An additional seven participants were excluded after analyzing their data from the visual lexical decision TMS experiment. 11 of 18 participants who received vOTC stimulation showed the expected slowdown on words, with an average increase of 40 ms for TMS relative to no-TMS trials (t (10) ϭ 4.0, p ϭ 0.003), similar to that seen previously (Duncan et al, 2010). The remaining seven either showed no effect of TMS or had faster RTs with stimulation, probably due to a nonspecific intersensory facilitation.…”
Section: Occipitotemporal Tmssupporting
confidence: 74%
“…Two versions of stimuli were created to guarantee that each stimulus was equally presented in TMS and no-TMS trials across participants. Previously, we have shown that rTMS to vOTC increased reaction times (RTs) in this task whereas stimulation of LOC had no significant effect on RTs (Duncan et al, 2010). Consequently, subjects who did not show a disruptive effect of ventral occipitotemporal rTMS on words were excluded from the analysis of the main experiment on the assumption that we had targeted the site incorrectly in these participants.…”
Section: Introductionmentioning
confidence: 99%
“…Others believe that the vOT is not dedicated to visual word form processing because it also responds to picture naming, repeating auditory words etc. (e.g., Devlin, Jamison, Gonnerman & Matthews, 2006;Duncan, Pattamadilok & Devlin, 2010;Price & Devlin, 2003Twomey, Duncan, Price & Devlin, 2011). The latter view considers the 1 Note that the direction of laterality within an activated region can be influenced by both excitatory and inhibitory connections from the LH/RH homologue areas.…”
mentioning
confidence: 99%
“…Other studies have measured the effects of stimulation on eye movements 63,64 . Most cognitive neuroscience experiments with TMS, however, use reaction times as their dependent measure 13,48,65,66 . Typically, the effects are on the order of tens of msec, or roughly a 10% change in reaction times 67 .…”
Section: Discussionmentioning
confidence: 99%
“…The duration of this disruption limits the temporal resolution of the technique to 10s of msec, roughly an order of magnitude coarser than electroencephalography (EEG) and magnetoencephalography (MEG). On the other hand, the timings observed in chronometric TMS studies tend to match those from invasive neurophysiological recordings better than EEG and MEG 9,13 . Presumably this is because EEG and MEG measure large scale neuronal synchrony that lags behind the earliest onset of activity , it was quickly adopted as a valuable tool for cognitive neuroscience.…”
Section: Introductionmentioning
confidence: 98%